Feminist Criminology and Women in Organized Crime: A Theoretical Exercise - Guerreiro,Ana (2022)
Abstract Since the 1970s, there has been an increase in the number of studies focused on women offenders. However, those associated with organized crime are still rare, despite the evidence of cases of women actively involved in criminal groups and playing particularly prominent roles. This article aims to present an integrated review of the known literature that emphasizes the presence of women as offenders in organized crime groups. To this end, we (i) discuss how academia evolved from an androcentric perspective to a feminist criminology approach, and (ii) outline the role played by women offenders in the context of organized crime and their functions inside the group.